Systematic work environment management: guidelines (Solna, 2003)
"This guide is based on the rules (Provisions and General Recommendations) on Systematic Work Environment Management issued by the Swedish Work Environment Authority and effective from 1st July 2001, superseding the former rules on Internal Control of the Working Environment, AFS 1996:6. It describes the basic elements of work environment management. That management needs to be adapted to your particular operation. ..."